Life cycle impact assessment (LCIA) using the ecological scarcity (Ecopoints) method: A potential impact analysis to potable water production - Sharaai, A.H.; Mahmood, Noor Zalina; Sulaiman, A.H. (Academic Journals, 2012)

(untitled)
Life cycle assessment (LCA) is a method use to analyze a product or a service from the beginning of the process where it is extracted until it is not useful anymore or it is known as cradle-to-grave analysis. LCA analysis includes the inventory collecting all types of emission and waste. After it is done, the inventory will be interpreted to the environmental impacts in life cycle impact assessment (LCIA). Two LCIA methods identified were "midpoint and endpoint" approaches. The ecological scarcity (ecopoints) is an LCIA method using "midpoint" approach. From the analysis to both life cycle stages, analysis for potable water production which was construction stage and production stage indicated that both stages contributed two main impacts namely: NOx and SOx. In the production stage, NOx and SOx were released from PAC production. On the other hand, for the construction stage, NOx and SOx were released from steel production process. Â© 2012 Academic Journals.